Case report: The activity of multi-kinase VEGF inhibitor, Pazopanib, in metastatic undifferentiated round cell sarcomas harboring EWSR1::CREM fusion: clinicopathological series of two cases and literature review - Campoverde, Leticia; Camacho, Felipe; Alessandrino, Francesco; Evans, Mark G.; Elliot, Andrew; Rosenberg, Andrew; Trent, Jonathan (Frontiers in Oncology, 2023)
Soft tissue sarcomas harboring EWSR1::CREM fusion are rare and challenging to treat. Pazopanib, a multi-tyrosine kinase inhibitor, is FDA-approved for advanced soft tissue sarcomas, but predictive biomarkers for its efficacy remain unidentified. We conducted a study on >240,000 neoplasms submitted to Caris Life Sciences (Phoenix, AZ) to detect rearrangements using whole transcriptome sequencing. Two board-certified pathologists performed histological reviews, and treatment/outcome information was collected. Among the identified cases (n = 18), we observed a diverse range of soft tissue sarcomas, including an intracranial myxoid mesenchymal tumor, mesothelioma, hyalinizing clear cell carcinomas of the head and neck, clear cell sarcomas, and undifferentiated round cell sarcomas, as well as histologically malignant tumors with epithelioid morphology. Notably, two undifferentiated metastatic abdominal round cell sarcoma cases demonstrated a significant partial sustained response and clinical benefit when treated with pazopanib. To investigate the genetic factors underlying the efficacy of pazopanib in these cases, next-generation sequencing and fluorescence in situ hybridization were analyzed for alterations in the tumors. The genomic analysis provided compelling evidence confirming the presence of EWSR1::CREM fusion in both cases, with no other pathogenic gene variants or copy number alterations detected. These cases demonstrate the potential of pazopanib as a promising therapeutic option for patients with EWSR1::CREM fusion-positive soft tissue sarcomas, including metastatic undifferentiated round cell sarcomas. The sustained clinical benefit and partial responses observed in these cases warrant further research to validate these findings and explore the wider utility of pazopanib in this rare and challenging subset of soft tissue sarcomas.